2013
DOI: 10.1371/journal.pone.0056308
|View full text |Cite
|
Sign up to set email alerts
|

EVI1 Inhibits Apoptosis Induced by Antileukemic Drugs via Upregulation of CDKN1A/p21/WAF in Human Myeloid Cells

Abstract: Overexpression of ecotropic viral integration site 1 (EVI1) is associated with aggressive disease in acute myeloid leukemia (AML). Despite of its clinical importance, little is known about the mechanism through which EVI1 confers resistance to antileukemic drugs. Here, we show that a human myeloid cell line constitutively overexpressing EVI1 after infection with a retroviral vector (U937_EVI1) was partially resistant to etoposide and daunorubicin as compared to empty vector infected control cells (U937_vec). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 65 publications
(130 reference statements)
1
28
0
Order By: Relevance
“…30 To address the question whether EVI1 would modulate the ATRA responses not only of its own and the RARb, but of a larger number of genes, RNA was extracted from 3 independent replicate cultures of U937_EVI1 and control U937_vec cells treated with 1 mM ATRA or an equivalent amount of its solvent DMSO for 24 h. Gene expression microarray analysis revealed that 453 genes were induced and 240 repressed by ATRA, and 44 genes were up-and 67 down-regulated by EVI1 at a false discovery rate (FDR) 63 of 0.05 (Fig 1A, B; Tables S1A, B). Genes were considered to exhibit an EVI1 modulated ATRA response if they fulfilled the following stringent criteria: the factor by which EVI1 significantly altered their expression in the presence of ATRA was equal to or greater than 2, and equal to or greater than the square of the factor by which EVI1 changed their mRNA levels in the absence of ATRA (see Materials and Methods for details).…”
Section: Evi1 Modulates Transcriptional Regulation By Atra Of a Substmentioning
confidence: 99%
See 1 more Smart Citation
“…30 To address the question whether EVI1 would modulate the ATRA responses not only of its own and the RARb, but of a larger number of genes, RNA was extracted from 3 independent replicate cultures of U937_EVI1 and control U937_vec cells treated with 1 mM ATRA or an equivalent amount of its solvent DMSO for 24 h. Gene expression microarray analysis revealed that 453 genes were induced and 240 repressed by ATRA, and 44 genes were up-and 67 down-regulated by EVI1 at a false discovery rate (FDR) 63 of 0.05 (Fig 1A, B; Tables S1A, B). Genes were considered to exhibit an EVI1 modulated ATRA response if they fulfilled the following stringent criteria: the factor by which EVI1 significantly altered their expression in the presence of ATRA was equal to or greater than 2, and equal to or greater than the square of the factor by which EVI1 changed their mRNA levels in the absence of ATRA (see Materials and Methods for details).…”
Section: Evi1 Modulates Transcriptional Regulation By Atra Of a Substmentioning
confidence: 99%
“…19 Analogously, experimental expression of Evi1 effected development of an MDS like disease, 20 and coexpression with other oncogenes such as HoxA9 C Meis1 or AML1 D171N caused AML 21,22 in murine bone marrow transplantation models. In vitro, EVI1 stimulated cell proliferation and inhibited differentiation and apoptosis in some experimental models, 12,16,20,[23][24][25][26][27][28][29][30][31] but elicited the opposite effects in others. 20,[31][32][33][34][35][36][37][38][39] This suggests that the fate of EVI1 overexpressing cells is influenced by lineage, maturation stage, cooperating molecular events, and/or environmental stimuli, and raises the possibility that it may be amenable to pharmacological modulation.…”
Section: Introductionmentioning
confidence: 99%
“…T-ALL cells exhibit increased apoptotic characteristics compared with BCP-ALL cells following exposure to cytotoxic drugs While p21 WAF1 induction has been demonstrated to inhibit apoptosis in various cancer histotypes with a range of sensitivity to cytotoxic stimuli, [5][6][7][8][10][11][12][13][14]28,42 the anti-apoptotic role of p21 WAF1 in p53-functional, chemotherapy-sensitive hematopoietic cells has still not been fully elucidated. We assessed the in vitro apoptotic responses of T-ALL and BCP-ALL PDXs and cell lines following exposure to etoposide or vorinostat.…”
Section: Resultsmentioning
confidence: 99%
“…10,11,13,28 One study used a p53 expressing leukemia cell line (HL-60), and here the disruption of p21 WAF1 function did not appreciably sensitize the cells to cytarabine. 48 The study herein is the first to report on the anti-apoptotic role of p21 WAF1 in a BCP-lineage leukemia cell line that was previously shown to have an intact p53 response to DNA damaging agents.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation